2019
DOI: 10.25046/aj040455
|View full text |Cite
|
Sign up to set email alerts
|

Design and Control of Autonomous Surface Vehicle to Support Bathymetry Survey in the Coastal Environment

Abstract: Traditionally bathymetry survey is generally carried out using boat, research vessel, and small craft which is equipped with the echo sounding instrument and involves many persons as the vessel crew. The survey method demands an additional cost because of the extra man power and an expensive vessel operational cost. An autonomous surface vehicle (ASV) which is equipped with echo sounder was developed by adopting small water-plane area twin hull (SWATH) hull form to support bathymetry survey in the coastal envi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…The water depth measurement device is completed by the digital dual-frequency depth sounder on board, which mainly uses ultrasonic waves to penetrate the medium and produce emission on the surface of different media, emits ultrasonic waves through the transducer, and measures the time difference between the emitted and reflected waves to measure the water depth [40]. The attitude sensor of the hull is used to correct the collected bathymetry data, eliminating the problem that the oscillation of the hull caused by wind and current during the measurement process makes the bathymetry data collected by the transducer mismatch with the GPS receiver plane data, ensuring that the measurement data is true and reliable [36,41]. The parameters of the unmanned vessel equipment are shown in Table 2.…”
Section: Unmanned Vessels and Monitoring Imaging Investigationsmentioning
confidence: 99%
“…The water depth measurement device is completed by the digital dual-frequency depth sounder on board, which mainly uses ultrasonic waves to penetrate the medium and produce emission on the surface of different media, emits ultrasonic waves through the transducer, and measures the time difference between the emitted and reflected waves to measure the water depth [40]. The attitude sensor of the hull is used to correct the collected bathymetry data, eliminating the problem that the oscillation of the hull caused by wind and current during the measurement process makes the bathymetry data collected by the transducer mismatch with the GPS receiver plane data, ensuring that the measurement data is true and reliable [36,41]. The parameters of the unmanned vessel equipment are shown in Table 2.…”
Section: Unmanned Vessels and Monitoring Imaging Investigationsmentioning
confidence: 99%
“…The current literature provides detailed ASV’s state of the art like [ 9 , 10 ] or, more recently, [ 11 , 12 ]. Regarding research and development, several relevant projects have been reported, carrying out different operations in aquatic scenarios like in [ 13 , 14 , 15 ].…”
Section: Related Workmentioning
confidence: 99%
“…Looking on current catamaran hull designs, the AERO4RIVER ASV [ 23 ] presents a new propulsion system based on aerial thrusters that allows allows navigation in very shallow waters. The pieces of work of [ 13 , 24 ], where the SWATH ASV is described, study the optimal catamaran hull form in order to provide low resistance and excellent station keeping performance in irregular head waves. In [ 25 ], the SWAMP ASV was presented highlighting the modularity and the extremely shallow depth navigation using a water pump as a propulsion system.…”
Section: Related Workmentioning
confidence: 99%